Multicultural cities, communication and transportation improvements: An empirical analysis for Italy - Cristina Cattaneo (Fondazione Eni Enrico Mattei (FEEM), 2012)
The paper investigates the determinants of cosmopolitan cities. The hypothesis tested empirically is whether gradual improvements in distant communication boost the generation of ethnically heterogeneous cities. Consequently to easier communication, movers increasingly rely on an enlarged community for identity transmission, rather than on localized peer effects of segregated environment. The empirical estimation provides support to the prediction of the model. A better access to the airports as well as improvements in internet communications are found to increase city ethnic diversity.
Keywords: R11; F22; 330; Multicutural Cities; Ethnic Diversity; Productivity